БЎЛАЖАК МУТАХАССИСЛАРНИНГ ИҚТИСОДИЙ – МАДАНИЯТИНИ РИВОЖЛАНТИРИШНИНГ ПЕДАГОГИК ШАРТ - ШАРОИТЛАРИ - Кучкорова, Н.М. (SCIENCE and SOCIETY, 2019)
The article focuses on the identification of pedagogical conditions for the development of economic culture of future specialists, including factors affecting the economic culture of beginning specialists. The author studies components of the formation of economic culture, technology of promoting economic culture, as well as the criteria selected for diagnosing the level of economic culture.